Application of Marketing Tools of Experiential Marketing in the Internet Sphere - Kurbatova (Tataryntseva), Yuliia; Ryabukha, Maria (IJERMT, 2017)
The article examines the concept of experiential marketing in the context of production promoting in the Internet sphere. Two groups of motives for user interaction with content in the network are identified - active and passive. The ways of satisfying the active motives of users in the development of a multimedia product are substantiated. Proposals by the use of tools for the concept of experiential marketing in the Internet sphere, such as values strengthening, coolhunting, brand development, design, theatricalization, personalization and dialogue have been formed.
Keywords: experiential marketing; experiential marketing tools; motives for interaction with content; Internet sphere; multimedia product